Analisis Faktor-Faktor Yang Mempengaruhi Alih Fungsi Lahan Sawah Seluruh Kecamatan Di Kabupaten Sukoharjo Tahun 2009-2015 - Riezka Haryanto, Ilham Basuki; , Dr. Didit Purnomo, SE. M.Si (2017)
Along with the development of the times, now agricultural land is on the wane. Many farmers are earning now turned into residential, industrial, shopping, tourist attractions and etc. But not easy to manage the wetland, there is need the human resources and an adequate tool so that the land can be used optimally. The most ares of Central Java province is wetland productive. However, at present many areas in Central Java province who use the land for the construction of infrastructure. Sukoharjo District is which one district with the most land conversion of the other districts in Central Java province. In this study discusses changes in wetland area between Sukoharjo districts in 2009-2015, as well as factors that affect the land use change. From the results of this research note that there are some districts that are experiencing land conversion. Land conversion is caused by several factors, namely the GDP, population and number of companies. The research looked at from two perspectives, the region analysis and the analysis based on the analysis performed edible period with panel data regression. Keywords: land area, GDP, population, the number of companies